Nanoparticle albumin-bound paclitaxel plus carboplatin induction followed by nanoparticle albumin-bound paclitaxel maintenance in squamous non-small-cell lung cancer (ABOUND.sqm): a phase III randomized clinical trial - Spigel, David; Jotte, Robert M.; Aix, Santiago Ponce; Gressot, Laurent; Morgensztern, Daniel; McCleod, Michael; Socinski, Mark A.; Daniel, Davey; Juan-Vidal, Oscar; Mileham, Kathryn F.; West, Howard; Page, Ray; et al. (Clinical lung cancer, 2021)
Background - We evaluated maintenance nanoparticle albumin-bound (nab) paclitaxel in the treatment of advanced squamous non-small-cell lung cancer. - Patients and Methods - Patients with treatment-naive squamous non-small-cell lung cancer received four 21-day cycles of nab-paclitaxel 100 mg/m2 on days 1, 8, 15 plus carboplatin area under the curve 6 on day 1 as induction therapy. Patients without disease progression after induction were randomized 2:1 to maintenance nab-paclitaxel 100 mg/m2 (days 1 and 8 every 21 days) plus best supportive care (BSC) or BSC alone. The primary endpoint was progression-free survival (PFS). Secondary endpoints included safety and overall survival (OS). - Results - Overall, 420 patients had received induction therapy; 202 (nab-paclitaxel plus BSC, 136; BSC, 66) had received maintenance therapy. Enrollment was discontinued after a preplanned interim futility analysis (patients could remain in the study at the investigator’s discretion). The median PFS was 3.12 months for nab-paclitaxel plus BSC and 2.60 months for BSC; the difference was not statistically significant (hazard ratio [HR], 0.85; 95% confidence interval [CI], 0.61-1.19; P = .36). The median OS (median follow-up, 24.2 months) was 17.18 months for nab-paclitaxel plus BSC and 12.16 months for BSC (HR, 0.70; 95% CI, 0.48-1.02; nominal P = .07). An updated analysis (median follow-up, 28.4 months) revealed a median OS of 17.61 months for nab-paclitaxel plus BSC and 12.16 months for BSC (HR, 0.68; 95% CI, 0.47-0.98; nominal P = .037). The most frequent grade 3 and 4 treatment-emergent adverse events for the entire study were neutropenia (53.1% [nab-paclitaxel plus BSC] vs. 50.0% [BSC]) and anemia (33.1% [nab-paclitaxel plus BSC] vs. 32.3% [BSC]). Only peripheral neuropathy had occurred in ≥ 5% of patients during maintenance therapy (13.1%; nab-paclitaxel plus BSC). - Conclusions - The results of the ABOUND.sqm did not meet the primary endpoint of PFS. An updated OS analysis revealed a trend favoring nab-paclitaxel plus BSC.